Analysis of the use of Adjustment Pads in Fine Adjustment of Geometry Settlement in Ballastless Track of Jakarta-Bandung High Speed Train (Case Study: K63+016~K63+035 Tegalega Area, Karawang, West Java) - Sinung Tri Nugroho; Heriyanto Wibowo; Salwa Ratu Haifa Hermawan (Jurnal Ilmu Multidisiplin, 2025)
On the ballastless track K63+016~K63+035 of the Jakarta-Bandung High Speed Railway (JBHSR) there is a decrease in geometry with the category of damage level reaching the limit set according to Regulation No. 11 PT KCIC Year 2023. The event was mostly caused by the irregularity of the lower structure due to dynamic loads. The procedure used is to perform fine adjustment using an adjustment pad according to the regulations listed in SOP No. 17 PT KCIC Year 2021 so that the decline can be overcome. Testing the effectiveness of using adjustment pads on geometry decline through hypothesis testing with the F test and t-test methods can determine how much influence between the two. The results of the analysis obtained a correlation value (ݑ) of 0.965 and a p-value of 0.000 <0.05 indicating that the use of adjustment pads has a very significant effect and a very strong correlation on geometry reduction.